(untitled) (Research, Society and Development, 2025)
The aim of this review was to analyze the scientific literature on the use of the Patient and Public Involvement (PPI) strategy in health research, considering its ethical relevance and its potential to improve study quality. A documentary review was conducted based on secondary sources from third-party articles, in a qualitative and minimally systematized study, characterized as a narrative literature review. The search was performed in December 2023 in PubMed/MEDLINE, SciELO, Google Scholar, and institutional websites, using Portuguese and English descriptors related to PPI and health research. Original articles, reviews, protocols, guidelines, and technical documents were included, with no restriction on publication date, while opinion pieces and non-evidence-based texts were excluded. A total of 55 documents were selected, comprising 40 scientific articles and 15 institutional reports or guidelines. The findings showed a predominance of systematic and scoping reviews that mapped engagement practices in different international contexts, as well as studies that demonstrated positive impacts of PPI on recruitment, retention, and dissemination processes. A wide range of implementation guides and tools were identified in countries such as the United Kingdom, the United States, and Canada, but only one national experience was found, highlighting the scarcity of consolidated practices in Brazil. It is concluded that PPI has the potential to expand the social and ethical relevance of health research in the country, contributing to greater applicability of results and strengthening citizen participation in the production of scientific knowledge.